INCIDÊNCIA DE DISPEPSIA FUNCIONAL, EM INDÍGENAS QUE VIVEM, EM CONTEXTO URBANO, NO MUNICÍPIO DE CAMPO GRANDE - MS - VILLALBA, Daniel Lucas Lopes Freitas; ABREU, Leticia de; ALMEIDA, Isis Marcondes Sodré de; QUADROS, Fatima Alice Aguiar; SAMPAIO, Gustavo Silva; SACCO, Carolina Maria Startari (ANAIS DO ENIC, 2022)
-